FENOMENA KELANGKAAN UREA DI SENTRA PRODUKSI PADI JAWA TENGAH TAHUN 2004 - Seno B asuki; Sarjana Sarjana (JURNAL LITBANG PROVINSI JAWA TENGAH, 2007)
Phenomenon of urea scar-cities in main area rice production is going on every year. As the urea is important matter of rice farm, the condition caused social uneasiness. In-depth study ofurea scarcities were done at 3 district rice producers, i.e.: Grobogan, Klaren and Banyumas on May –June 2004( while scar-cities is going on) to find out ofurea scarcities problems at every trade chain. The method used problem investigation at farmer level up to producer and to clarification with agency interrelated. The data collected analyzed by graphical and tabular presentation. Result of ihis study are: a) critical condition ofurea scarcities caused by lack information of news about farm dynamics b) planning of urea needs are based capacious area and crop pattern formerly year c) socialization ofrayon supply to consumer are not reach and d) supervision go on not yet. In order, consumer opinion safe and certainty needs information of actual urea stock and anticipation are based on change offarm strategies environmental such as: climate anomaly